2021
DOI: 10.1016/j.celrep.2021.109522
|View full text |Cite
|
Sign up to set email alerts
|

The angiopoietin-Tie2 pathway regulates Purkinje cell dendritic morphogenesis in a cell-autonomous manner

Abstract: Highlights d Ang1 and Ang2 are expressed in cerebellar neural and endothelial cells, respectively d The angiopoietin receptor Tie2 is expressed in blood vessels and Purkinje cells d Tie2 signaling regulates PC dendritic morphogenesis in a cellautonomous manner d PCs network functionality is altered in PC specific Tie2deficient mice

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“… 17 This type of paracrine signaling is common in the Angpt/Tie2 pathway and occurs, for example, between Purkinje, endothelial, and neural cells. 43 scRNAseq data from adult mice revealed that some TM cells had overlapping expression of both Angpt1 and Angpt4, whereas most TM cells expressed only either one (e.g., among the Angpt1 + JCT cells, 10.5% simultaneously expressed Angpt4, being 50% of Angpt4 + JCT cells). The lack of any SC defect in the Angpt1 fl/fl ; Angpt4 Cre/Cre mice, in which Angpt4 promoter–driven Cre expression (starting at P10) would prevent Angpt1 expression from the floxed allele if occurring in the same cells, also supports this observation.…”
Section: Discussionmentioning
confidence: 99%
“… 17 This type of paracrine signaling is common in the Angpt/Tie2 pathway and occurs, for example, between Purkinje, endothelial, and neural cells. 43 scRNAseq data from adult mice revealed that some TM cells had overlapping expression of both Angpt1 and Angpt4, whereas most TM cells expressed only either one (e.g., among the Angpt1 + JCT cells, 10.5% simultaneously expressed Angpt4, being 50% of Angpt4 + JCT cells). The lack of any SC defect in the Angpt1 fl/fl ; Angpt4 Cre/Cre mice, in which Angpt4 promoter–driven Cre expression (starting at P10) would prevent Angpt1 expression from the floxed allele if occurring in the same cells, also supports this observation.…”
Section: Discussionmentioning
confidence: 99%
“…4b ). Dnmt3a deficiency also led to downregulation of axon growth-inhibitory signals, such as Semaphorin 4 (SEMA4) 38 , and upregulation of synapse and axon growth-promoting signals, angiopoietin (ANGPT) 39,40 and secreted phosphoprotein 1/osteopontin (SPP1) 41 ( Fig. 4a ).…”
Section: Main Textmentioning
confidence: 99%